The remediated scene: hypermediation and immediacy in two Latin American theater representations of the 21st century (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
Digital technologies have transfigured the field of theatrical art and have been producing a series of mutations that affect the perceptive tradition of live performance. To approach these new modes of communication that theater establishes today, strengthened in the intersection with these technologies, we will turn to the concept of remediation proposed by Bolter and Grusin, to examine two representative performances of the Latin American scene of the 21st century (Sin Sangre, by Teatrocinema, and Othelo, by Buendía Theatre), the ways in which the opacity of the medium (hypermediation) or its transparency (immediacy) contribute to the construction of technological poetics on the scene itself.
Keywords: Theater; digital; technologies; remediation; hypermediation; immediacy